The Correlation Between Philosophy, Science And Reading Learning - Winda Widyaningrum; Aceng Rahmat; Saifur Rahman (Jurnal Sains Sosio Humaniora, 2021)
Philosophy is the mother of all sciences. Philosophy, in this case, is more of a universal, comprehensive, and fundamental thought, while other sciences are more specific or special thoughts because they are limited to objects and their unique point of view. Philosophy and science can meet each other because both use the method of reflective thinking in an attempt to deal with the facts of the world and life. Both display a critical attitude, with an open mind and an impartial will, to know the nature of truth. Philosophy requires language as a means of communicating ideas and also as an object of study in philosophy. While language also really needs philosophy as a means or method to analyze systems to get solutions to solving linguistic problems. Reading learning is very important so that a text or statement of a philosopher can be more easily understood. Ignorance of text and context in discourse will lead to confusion in understanding science. If science can be understood well it will add insight and can be shared with others. People with good reading comprehension will bring benefits to others. So it can be concluded that there is a correlation between philosophy, science and reading learning.